GPR Preprocessing Methods to Identify Possible Cavities in Lateritic Soil - Savita, S.J; Anbazhagan, P; Pallavi, Andhe (International Journal of Computer Sciences and Engineering, 2025)
Lateritic soils is formed by soft sediments, entangled between rigid to soft lateritic rock, and are seeped due to the entry of water in rainy seasons forming cavities which span over large lengths and considerable depth. Mainly in southern and central parts of India the Lateritic soils are formed. The proposed research work aims at the detection of cavities and formation of sink holes in lateritic soil. The data used in this proposed work is obtained from project site in Kannur District, Kerala State, India. To detect the heterogeneities in lateritic soils and formation of cavities, a Geophysical survey method, namely ground penetrating radar (GPR) with 100 MHz and 500 MHz (for confirmative survey) Ground Coupled antennae were used. The proposed work involves two dimensional 2D image pre-processing of the radargram obtained from GPR. The pre-processing involves data editing, time zero correction, Dewow filter, gain control, Background noise removal and edge detection to improve the detection of cavities in lateritic soil. This provides a means for interpreting the raw GPR data.